Dual-Energy Computed Tomography Detection of Cardiovascular Monosodium Urate Deposits in Patients With Gout - Klauser, Andrea Sabine (JAMA Cardiol, 2019)
IMPORTANCE: The prevalence of gout has increased in recent decades. Several clinical studies have demonstrated an association between gout and coronary heart disease, but direct cardiovascular imaging of monosodium urate (MSU) deposits by using dual-energy computed tomography (DECT) has not been reported to date. OBJECTIVE: To compare coronary calcium score and cardiovascular MSU deposits detected by DECT in patients with gout and controls. DESIGN, SETTING, AND PARTICIPANTS: This prospective Health Insurance Portability and Accountability Act–compliant study included patients with gout and controls who presented to a rheumatologic clinic from January 1, 2017, to November 1, 2018. All consecutive patients underwent DECT to assess coronary calcium score and MSU deposits in aorta and coronary arteries. In addition, cadavers were assessed by DECT for cardiovascular MSU deposits and verified by polarizing microscope. Analysis began in January 2017. MAIN OUTCOMES AND MEASURES: Detection rate of cardiovascular MSU deposits using DECT in patients with gout and control group patients without a previous history of gout or inflammatory rheumatic diseases. RESULTS: A total of 59 patients with gout (mean [SD] age, 59 [5.7] years; range, 47-89 years), 47 controls (mean [SD] age, 70 [10.4] years; range, 44-86 years), and 6 cadavers (mean [SD] age at death, 76 [17] years; range, 56-95 years) were analyzed. The frequency of cardiovascular MSU deposits was higher among patients with gout (51 [86.4%]) compared with controls (7 [14.9%]) (χ(2) = 17.68, P < .001), as well as coronary MSU deposits among patients with gout (19 [32.2%]) vs controls (2 [4.3%]) (χ(2) = 8.97, P = .003). Coronary calcium score was significantly higher among patients with gout (900 Agatston units [AU]; 95% CI, 589-1211) compared with controls (263 AU; 95% CI, 76-451; P = .001) and also significantly higher among 58 individuals with cardiovascular MSU deposits (950 AU; 95% CI, 639-1261) compared with 48 individuals without MSU deposits (217 AU; 95% CI, 37-397; P < .001). Among 6 cadavers, 3 showed cardiovascular MSU deposits, which were verified by polarizing light microscope. CONCLUSION AND RELEVANCE: Dual-energy computed tomography demonstrates cardiovascular MSU deposits, as confirmed by polarized light microscopy. Cardiovascular MSU deposits were detected by DECT significantly more often in patients with gout compared with controls and were associated with higher coronary calcium score. This new modality may be of importance in gout population being at risk from cardiovascular disease.